Venous thromboembolism: Annualised United States models for total, hospital-acquired and preventable costs utilising long-term attack rates - Mahan, Charles E.; Borrego, Matthew E.; Woersching, Alex L.; Federici, Robert; Downey, Ross; Tiongson, Jay; Bieniarz, Mark C.; Cavanaugh, Brendan J.; Spyropoulos, Alex C. (Thrombosis and Haemostasis, 2012)
Healthcare reform is upon the United States (US) healthcare system. Prioritisation of preventative efforts will guide necessary transitions within the US healthcare system. While annual deep-vein thrombosis (DVT) costs have recently been defined at the US national level, annual pulmonary embolism (PE) and venous thromboembolism (VTE) costs have not yet been defined. A decision tree and cost model were developed to estimate US health care costs for total PE, total hospital-acquired PE, and total hospital-acquired “preventable” PE. The previously published DVT cost model was modified, updated and combined with the PE cost model to elucidate the same three categories of costs for VTE. Direct and indirect costs were also delineated. For VTE in the base model, annual cost ranges in 2011 US dollars for total, hospital-acquired, and hospital-acquired “preventable” costs and were $13.5-$27.2, $9.0-$18.2, and $4.5-$14.2 billion, respectively. The first sensitivity analysis, with higher incidence rates and costs, demonstrated annual US total, hospital-acquired, and hospital-acquired “preventable” VTE costs ranging from $32.1-$69.3, $23.7-$51.5, and $11.9-$39.3 billion, respectively. The second sensitivity analysis with long-term attack rates (LTAR) for recurrent events and post-thrombotic syndrome and chronic pulmonary thromboembolic hypertension demonstrated annual US total, hospital-acquired, and hospital-acquired “preventable” VTE costs ranging from $15.4-$34.4, $10.3-$25.4, and $5.1-$19.1 billion, respectively. PE costs comprised a majority of the VTE costs. Prioritisation of effective VTE preventative strategies will reduce significant costs, morbidity and mortality within the US healthcare system. The cost models may be utilised to estimate other countries’ costs or VTE-specific disease states.
Keywords: Cost model; venous thomboembolism; pulmonary embolism; deep-vein thrombosis; preventable costs; annualised; long-term attack rates; adverse event